The evolution of the tattoo in defiance of the immutable definition of deviance: current perceptions by law enforcement of tattooed arrestees. Issue 8 (3rd August 2018) - Camacho, Jocelyn; Brown, Wyatt
ABSTRACT: Tattoos have made their way from prisons to fashion runways, but are they still perceived by law enforcement as marks of deviance? The purpose of this study is to examine law enforcement arrest patterns to determine the relationship between tattoos and offense charges. This study analyzes a random sample of arrestees from a large county in the Southern U.S. Using logistic regression models, the relationship between tattoos, tattoo location, number of offense charges, and severity of offense charges is examined.